Breast cancer mortality in urban and rural female population in Poland in years 2002-2011 - Krzyżak, Michalina; Maślach, Dominik; Pogorzelska, Patrycja; Piekutowska, Sylwia; Szpak, Anna (Polish Journal of Public Health, 2013)
Introduction. Variation in female breast cancer incidence and mortality between urban and rural areas is one of the inequalities in the health of the Polish population.Aim. The aim of the study was to analyse the differences in breast cancer mortality among urban and rural female population in Poland in years 2002-2011.Material and Methods. The study material was based on the data from the Central Statistical Office of Poland on the number of breast cancer deaths registered in Poland for the period 2002-2011. Mortality rates for urban and rural populations: crude and age-specific, as well as age-standardised (ASR) were calculated and expressed per 100 000 women at risk. Mortality differences related to the place of residence were presented with the use of urban/rural ratio. Time trends for mortality rates in urban and rural population in years 2002-2011 were analysed. The changes in mortality rates were evaluated using the joinpoint model.Results. Average annual ASR in urban areas amounted 15.6/100 000 (crude 29.2/100 000), in rural – 12.4/100 000 (crude 20.9/100 000). Urban/rural ratio for ASR was 1.26 [95% CI: 1.13 to 1.39] and for crude rate it was 1.39 [95% CI: 1.31 to 1.48]. ASR in urban area significantly decreased by 1.0% per year [95% CI: 1.6 to -0.5]), in rural areas mortality decreased only by 0.3% per year.Conclusions. Breast cancer mortality in Poland was markedly higher in urban female population. However, age- standardised mortality rate was slowly decreased among women living in urban areas. In rural areas the mortality trend decreased slightly and those changes were statistically insignificant.